2006
DOI: 10.1088/0957-4484/17/15/057
|View full text |Cite
|
Sign up to set email alerts
|

Conical nanopore membranes: solvent shaping of nanopores

Abstract: We have undertaken a systematic investigation of the influence of ethanol on the shape of conical pores produced by the track-etch technique in poly(ethylene terephthalate) films. We have found that the cone angle of the conical nanopore generated is dependent on the amount of ethanol present in an alkaline etching solution. By varying the percentage of ethanol in the etch solution, precise control over the geometry of the conical nanopore and nanomaterials templated within these pores can be attained. We prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 25 publications
0
81
0
Order By: Relevance
“…The application of a potential across the membrane is stopped as soon as a monitoring ammeter records an increase in the current that passes through the membrane up to reaching a pre-set value, typically 1 mA (40). The membrane is then immediately immersed (both sides) in the stopping medium, thus blocking the asymmetric etching.…”
Section: 3)mentioning
confidence: 99%
See 2 more Smart Citations
“…The application of a potential across the membrane is stopped as soon as a monitoring ammeter records an increase in the current that passes through the membrane up to reaching a pre-set value, typically 1 mA (40). The membrane is then immediately immersed (both sides) in the stopping medium, thus blocking the asymmetric etching.…”
Section: 3)mentioning
confidence: 99%
“…The membrane is then immediately immersed (both sides) in the stopping medium, thus blocking the asymmetric etching. At the end of the process, conical nanopores of controlled shape are obtained (37,40). It was also shown that the addition of alcohols (such as methanol, ethanol, or propanol) to the etch solution allows further control of the etching rate (24) and the V B /V T ratio (40, 41).…”
Section: 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Other investigations in their laboratory have created asymmetric nanopores in track-etched polymer membranes via etching of the nuclear damage tracks with KOH/ethanol from one side of the membrane with an acidic "stop" solution opposite. 22 Half-angles up to 4.4°were obtained yielding entrance to exit aperture ratios as large as 2:1.…”
Section: Single Nanocapillary Experimentsmentioning
confidence: 99%
“…The swelling process can be explained by a diffusion process of alcohol into the polymer chains along the tracks. Ethanol effects a destruction of the two-dimensional order of the polycarbonate chains, which are normally well packed and parallel [29].…”
Section: Hierarchical Shapes -Nanowhiskersmentioning
confidence: 99%